Persepsi Orang Dengan Gangguan Penggunaan Zat (ODGPZ) terhadap Kebijakan Rehabilitasi Narkotika - Agus Pratama; Al Zuhri; Muntaha Mardhatillah; Ilham Mirza Saputra (Asosiasi Ilmuwan Administrasi Negara (ASIAN), 2023)
This study was undertaken in order to ascertain the opinions of ODGPZ and to introduce narcotics rehabilitation policies to them, so that the information provided to respondents can provide insight into the world of rehabilitation, particularly in terms of narcotics rehabilitation rules and regulations. The topic of this study is quite sensitive and has a private personality, which makes it difficult to find informants ready to share their stories, particularly about narcotics. The authors used a descriptive qualitative method in this study and were able to collect 4 (four) respondents using the snowball sampling methodology. The findings of this study show that respondents lacked information about narcotics rehabilitation policies, causing them to be unaware of the contents of these rules. The authors then goes on to explain the key points of the rehabilitation policy, concluding that the policy is an effort or form of the government to protect abusers from becoming addicted to narcotics.